Flexible thin films based on poly(ester imide) materials for optoelectronic applications. Issue 1 (28th August 2021) - Serbezeanu, Diana; Homocianu, Mihaela; Macsim, Ana‐Maria; Enache, Alexandru Alin; Vlad‐Bubulac, Tăchiță
Abstract: A series of high‐performance poly(ester imide)s bearing cycloaliphatic moieties was manufactured by a two‐step procedure via solution polycondensation of an aromatic–aliphatic dianhydride containing preformed ester units and cyclohexanone ring in the main chain, with various aromatic diamines. The new dianhydride monomer, namely 2‐oxocyclohexane‐1, 3‐bis[4, 4′‐bis(trimellitate)benzylidene] dianhydride, was synthesized by the reaction between 2, 6‐bis(4‐hydroxybenzylidene)cyclohexanone and trimellitic anhydride chloride. The chemical structure of the resulting dianhydride was confirmed by means of Fourier transform infrared, 1 H NMR and 13 C NMR spectroscopies. The poly(ester imide)s from the series exhibited water uptake capacity in the range 3.45–10.09%. The onset temperatures, corresponding to the first detected thermal weight loss in the samples, ranged from 367 to 441 °C. Besides the cycloaliphatic moieties coming from the dianhydride monomer, the other aliphatic segments present in the diamine structures were responsible for improved optical performance in the resulting poly(ester imide)s, the transmittance being higher than 80% at 684 nm. © 2021 Society of Industrial Chemistry. Abstract : High‐performance poly(ester imide)s bearing cycloaliphatic moieties were developed. Thin flexible films were produced via casting‐from‐solution technique. Improved transparency was obtained in the series. Varied emission wavelengths could be achieved by chemical structure design.